Bond behavior and ultimate capacity of notched concrete beams with externally-bonded FRP and PBO-FRCM systems under different environmental conditions. (30th December 2020) - De Domenico, Dario; Urso, Santi; Borsellino, Chiara; Spinella, Nino; Recupero, Antonino
Highlights: Bond behavior of CFRP and PBO-FRCM systems comparatively analyzed. Different environmental conditions in terms of temperature and humidity. Novel notched beam test setup with externally bonded composite systems adopted. Analytical procedure to determine stress-global slip curve as in direct shear test. Different sensitivity of FRP and FRCM to high temperature conditions. Abstract: The influence of environmental conditions on the bond behavior and ultimate capacity of strengthening composite systems applied to concrete substrates is investigated. Two different systems are analyzed, namely fiber-reinforced polymer (FRP) system with carbon sheet and epoxy resin (CFRP), and fiber-reinforced cementitious matrix (FRCM) system with polybenzoxole (PBO) grid and cement-based mortar. The experimental campaign comprises three-point bending tests on 24 notched beams with the strengthening system being externally bonded onto the bottom face of the beam in order to selectively study the bond behavior with no tensile contribution of concrete. In addition to classical curing process in air at environmental conditions, two wet curing procedures are studied, namely partial immersion in water at 30 °C and 50 °C and 100% relative humidity for a period of 31 days. Results in terms of load-displacement curves, failure modes and ultimate capacity are critically analyzed so as to highlight the influence of the conditioning factors (humidity and temperature) on the bond behavior at the concrete-composite interface of the two strengthening systems comparatively. For the relatively short duration of the partial immersion process considered in this experimental campaign, the FRCM system is not sensitive to environmental conditioning, whereas the FRP system is only sensitive to curing temperatures close to the glass transition temperature of the resin/primer. For the PBO-FRCM system, an indirect method to evaluate the stress-global slip curve is elaborated in this study through an analytical procedure based on kinematics considerations, which allows a comparison between results from the proposed notched beam test setup and results from alternative single-lap or double-lap shear tests that are more widely used in the literature.